PRAKTIK BALANCED SCORECARD SEKTOR PUBLIK: SISTEM PENGUKURAN KINERJA UNTUK MENINGKATKAN PERFORMA ORGANISASI - Ali Tafriji Biswan; Syahirul Alim (STIE Wiyatamandala, 2021)
This study aims to explore performance based on the Balanced Scorecard in the public sector, namely the Center for Information Systems and Financial Technology. Although initially the BSC measurement system was designed for the private sector from the perspective of customer, financial, internal business processes, and learning & growth, public organizations have also adopted it, of course, with modifications to suit organizational needs. The Ministry of Finance began implementing the Balanced Scorecard in 2007, and until now it has covered all levels of the organization, including the Center for Information Systems and Financial Technology. The study results show a summary of the perspectives into three perspectives of stakeholders (customers), internal business processes, and learning & growth; The target achievement of the Key Performance Indicators (KPI) based on the BSC can be achieved, thus encouraging improvements and improvements in future performance.